RANCANG BANGUN GAME TREASURE OF LABYRINTH DENGAN ALGORITMA BACKTRACKING BERBASIS ANDROID - Rio Andriyat Krisdiawan; Ramdoni Ramdoni; Aji Permana (NUANSA INFORMATIKA, 2020)
Games are one of the entertainment media which is the choice of almost everyone to get rid of boredom or just fill in spare time, there are also games used as hobbies and moreover games are now used as electronic sports (e-sports). Currently the game has many types of games, one of which is a type of puzzle game (puzzle). One puzzle game is a maze game. The labyrinth is a puzzle that has a complex branching form and has many dead ends. At the moment there are many labyrinth type games, but rarely are labyrinth games equipped with characters, enemies and a dynamic maze that can change if the game is repeated. To create a labyrinth game that has a dynamic labyrinth arena requires a labyrinth generator or can be called a labyrinth generator by utilizing the backtracking algorithm. This algorithm is powerful enough to be used in some problem solving and also to provide artificial intelligence in the game. The software methodology used in making games is the GDLC (Game Development Life Cycle). GDLC is a game development model that adopts an iterative approach consisting of 6 development phases, starting from the innitiation, pre-production, production, testing, beta and realese phases. for the generation of the labyrinth arena using the Backtracking algorithm while for testing this game uses the UAT (User Acceptment Test). The results of this study in the form of an adventure game based on a maze puzzle that is applied to mobile android. This game is played to train players in problem solving and entertainment facilities.Keywords: Puzzle Game, GDLC (Game Development Life Cycle), Backtracking Algorithm, Android